METAFORA DALAM PUISI MISTIK KARYA EDGAR ALLAN POE - Djindan, Nabillah (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Poetry is the oldest form of literary genres. It can be based on life experiences. Mystique is one life experience that can be expressed in a poem. It is important for the readers to understand how a poet uses words, how a poet puts fresh vigors and new meanings into words. Metaphor is one of the poet's ways of using words to give pleasure to the readers. Edgar Allan Poe is an American Poet who used a lot of metaphors in his mystique poems. So, the aims of this research are to analyze the uses of metaphor and to interprete the meaning of metaphor in his mystique poems. All the data were collected using literature research methods that have relations to the object of research. The writer used intrinsic approach to analyze these poems and to show the use of metaphor in Edgar's mystique poems. The result of this study shows that Edgar uses a lot of metaphor in his poems. The metaphor in his mystique poems is about mystique that expresses empty feelings in his whole life. --------------------------------------------------------------------------------------------------- Keywords : Edgar Allan Poe, Metaphor, Mystique Poems